Introduction to Dossier. International Migrations in Latin America: Critical Views on the Production of a Field of Knowledge - Gioconda Herrera; Ninna Nyberg Sorensen (Íconos)
This article presents a reflection from three dimensions on epistemological and political logics that crosscut the studies on migrations in Latin America: 1) the increasing heterogeneity of flows and the need to rethink the conceptual categories from which migrations are addressed; 2) the dialogue and appropriation of analytical frameworks produced in other regions in Latin American studies; and 3) the political agendas of the States in the region and in the North, and their selective influence on the production of knowledge. The objective is to offer a general reflection on the production of the field of studies on migrations in Latin America to serve as a context for the analysis of the five articles presented in this dossier of Íconos. Revista de Ciencias Sociales.